(untitled) (Scientific journal of the Fergana State University, 2023)
Religious awareness, in addition to the knowledge about the world, assists in creating one’s life norms and rules. Language is preliminary in perceiving religious knowledge. In this article the role of language in cognizing the world is elucidated and the main religious concepts of the Uzbek language are analyzed.